A framework for disaster mitigation networks - Yamamoto, Osamu (ASEAN engineering journal)
The existing communication infrastructure could be destroyed during a disaster and this could lead to the disruption of communication activities. Communication is extremely important during disasters; therefore it is vital that a temporary network is quickly setup to restore communication activities. Temporary networks could be setup using programmable sensor nodes. In this paper, we present SafeNet, a framework for disaster mitigation networks using programmable sensor nodes. We discussed several aspects such as: i) placement of sensor nodes, ii) modes of operation, and iii) the required components.